A case study of a Spanish fashion Communication Agency: Tal Cual Comunicación - Martín Cerro, Ruth (2015)
The purpose of this paper is to research how Spanish fashion works. A case study of a Spanish fashion communication agency: Tal Cual Comunicación is meant to show the necessity and the importance of communication in fashion. Fashion is one of industries in Spain and needs to have a strategic plan of communication, which would be led by professional people who work either at a communication department or communication agency specialist in fashion. We can understand through this study case how this industry works and deal with a communication agency by working on a communication strategy plan. To sum up, we can see that both the objectives and the hypothesis match with the conclusions. This means that there is a necessity of a personal treatment from a communication agency to its clients.